Analysis of Biochemical Parameters of Amaranthus Tristis during Seed Germination using CaCl2, Bijamrita and Cyanospray (Global Journal of Science Frontier Research, 2013)
The influence of inorganic and organic fertigations during seed germination on A. tristis was evaluated in the present study. Effect of different concentrations of chemical (CaCl 2 ) and different organic fertilizers such as Bijamrita and cyanospray on seed germination at room temperature were analyzed for protein, amino acid and amylase enzyme in both untreated and treated ways respectively. Our findings indicated that during germination the amount of amylase and amino acid increased at 48th hrs in combination with 25% Bijamrita and 0.3% cyanospray (50:50) when compared with other treatments, but, the protein content was significantly reduced during germination when compared with non-germinated seeds. Possible optimum concentration was determined to induce seed germination and thereafter growth of seedlings.
Keywords: protein; amino acids; amylase; cyanospray; bijamrita; seed germination; A tristis